Understanding the fundamentals of the U.S. presidential election system - Belenky, Alexander S. (Springer Berlin Heidelberg, 2012)
This is the first book on the U.S. presidential election system to analyze the basic principles underlying the design of the existing system and those at the heart of competing proposals for improving the system. The book discusses how the use of some election rules embedded in the U.S. Constitution and in the Presidential Succession Act may cause skewed or weird election outcomes and election stalemates. The book argues that the act may not cover some rare though possible situations which the Twentieth Amendment authorizes Congress to address. Also, the book questions the constitutionality of the National Popular Vote Plan to introduce a direct popular presidential election de facto, without amending the Constitution, and addresses the plan’s “Achilles’ Heel.”  In particular, the book shows that the plan may violate the Equal Protection Clause from the Fourteenth Amendment of the Constitution. Numerical examples are provided to show that the counterintuitive claims of the NPV originators and proponents that the plan will encourage presidential candidates to “chase” every vote in every state do not have any grounds. Finally, the book proposes a plan for improving the election system by combining at the national level the “one state, one vote” principle – embedded in the Constitution – and the “one person, one vote” principle. Under this plan no state loses its current Electoral College benefits while all the states gain more attention of presidential candidates. Introduction -- The constitutional origins of the election system -- Should the underlying concepts of the 1787 Great Compromise be honored.? -- Stubborn numbers: how much of a say does the nation have in presidential elections? -- What if? Constitutional puzzles, weird outcomes, and possible stalemates in presidential elections -- “Winner-take-all:” is it as bad as they paint it to be? -- Can the National Popular Vote plan succeed? -- When every voter gains and no state loses: can the “one person, one vote” and the “one state, one vote” principles coexist? -- How existing election rules may aﬀect the structure of election campaigns -- Conclusion -- References -- Appendices.